Paleontology in the 21st Century - Schweitzer, Mary H.; Kaya, Ferhat (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue highlights fundamental changes to the questions that we can ask about both the recent past and deep time. Delve into the forefront of paleontological research with this Special Issue reprint. Renowned paleontologists from around the world share groundbreaking insights into ancient life on Earth. Discover the latest advances in fossil discovery, analytical techniques, interdisciplinary collaborations, and technological innovations that are shaping our understanding of evolution and the Earth's history. This collection of cutting-edge research is a must-read for scientists, researchers, and enthusiasts interested in the dynamic field of paleontology in the modern era.